IMAGING DIAGNOSIS–PULMONARY‐TRACHEOBRONCHIAL PROLAPSE IN A NEW CALEDONIAN GIANT GECKO (RHACODACTYLUS LEACHIANUS). Issue 6 (13th May 2013) - Hoey, Seamus; Keller, Dominique; Chamberlin, Tamara; Pinkerton, Marie; Waller, Kenneth; Drees, Randi
Abstract : A 3‐year‐old male New Caledonian giant gecko, or Leach's gecko ( Rhacodactylus leachianus ) presented with acute lethargy and coelomic distention. Findings from survey radiographs and an upper gastrointestinal tract contrast study were consistent with severe aerophagia, a collapsed left lung, and hyperinflation of the right lung due to suspected bronchial obstruction. The gecko was treated with conservative medical management, but was found dead 5 days after presentation. Necropsy findings showed intussusception of the proximal left lung into the left mainstem bronchus and trachea.